Hubungan Interaksi Sosial Siswa di Sekolah dengan Prestasi Belajar IPS Siswa Kelas IV SD Inpres 17 Bajoe - Ainun Fitri; muh Idris Jafar; sudirman sudirman (Universtas Negeri Makassar, 2021)
This study is a correlation study that aims to know the relationship of social interaction of students in schools with the achievement of learning IPS grade IV SD Inpres 17 Bajoe Tanete Riattang Timur District Bone. The research approach is a quantitative approach. This type of research is correlation research. Research data were obtained through questionnaires and documentation. The population in the study were all grade IV students of SD Inpres 17 Bajoe Tanete Riattang Timur Subdistrict Bone District in the 2020/2021 school year as many as 48 students. The numbered off 48 students were samples. Data analysis technique is Correlation Analysis, the results showed the relationship of social interaction of students in schools with the achievement of learning IPS grade IV SD Inpres 17 Bajoe Tanete Riattang Timur Bone District belongs to the moderate category and there is a significant relationship.Â Â